Life stage hypothesis modeling determines insect vulnerability during developmental life stages to climate extremes - J. Simone Durney; Diane M. Debinski; Stephen F. Matter (Ecosphere)
Abstract Butterflies are important bioindicators that can be used to monitor the effects of climate change, particularly in montane environments. Changes in butterfly population size over time, reflective of indicator life stages, can signal changes that have occurred or are occurring in their environment indicating ecosystem health. From the perspective of understanding butterflies as bioindicators in these systems, it is essential to identify influential environmental variables at each life stage that have the greatest effect on population dynamics. Life stage hypothesis modeling was used to assess the effects of multiple temperature and precipitation metrics on the population growth rate of a Parnassius clodius butterfly population from 2009 to 2018. Extreme maximum temperatures during the larval‐pupal life stages were identified to have a significant negative effect on population growth rate. We speculate that higher temperatures during the spring ephemeral host plant's flowering, and P. clodius' larval stage, may lead to earlier plant senescence and lower P. clodius growth. Because Parnassius butterflies are well studied from a global perspective, results may aid in understanding the potential indicator life stages of other insect species in montane environments to climatic changes. Findings from this study demonstrate the value in assessing a butterfly species' response to short‐term weather variation or long‐term climatic changes at each life stage in order to protect and conserve insects and their interactions with other organisms.